Vampires in Halyna Pahutiak's contemporary Ukrainian fiction: biting into the global myth - Krys, Svitlana (My University, 2018)
This article discusses the manner in which the vampire fiction of contemporary Ukrainian author I lalyna Pahutiak enters into a dialogue with the global vampire discourse whose core or “cultural capital” finds its origins largely in Bram Stoker's novel Dracula (1897). Through discussion of thematic, stylistic, and structural similarities and differences between Pahutiak and Stoker's portrayals of the vampire myth, my paper sheds light on the conscious mythmaking strategies that Pahutiak employs to return the vampire symbolically from the West to Eastern Europe where it originated, and reassess the core characteristics of the Dracula myth.
Keywords: vampire myth; Bram Stoker; Dracula (1897); contemporary Ukrainian literature; Halyna Pahutiak (1958-); Slavic folklore; Eastern Europe